2011
DOI: 10.1007/s12540-011-0614-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical degradation of API X65 pipeline steel by exposure to hydrogen gas

Abstract: Hydrogen-induced degradations have generally been investigated through the ex situ testing of cathodically hydrogen-charged specimens. However, the cathodic charging cannot realize damage accumulation by gaseous hydrogen in transportation pipelines. Thus, we designed an ampule specimen which enables an in situ tensile test containing gaseous hydrogen. Ampule specimens made of API (American Petroleum Institute) X65 pipeline steel showed significant reductions of 3.4 % and 4.1 %, respectively, in their ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…This observation is consistent with the contribution of hydrogen cracking to fracture at a lower stress compared to testing in the absence of hydrogen. The NTB sample showed the maximum embrittlement index, consistent with the results of three-point bend (TPB) testing reported in Hejazi et al 27 Although there are reports of tensile testing in the presence of gaseous hydrogen of X65 steel at the room temperature, 28 stainless steel at −20 to −250°C 31 and medium carbon steel at room temperature, 32 tensile testing of X70 steel under hydrogen at elevated temperatures (50 and 100°C) has not previously been reported. Since pipelines located in the desert environment are subject to deformation at low strain rates and can reach 50°C and over, the current work constitutes an attempt to simulate this service condition.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This observation is consistent with the contribution of hydrogen cracking to fracture at a lower stress compared to testing in the absence of hydrogen. The NTB sample showed the maximum embrittlement index, consistent with the results of three-point bend (TPB) testing reported in Hejazi et al 27 Although there are reports of tensile testing in the presence of gaseous hydrogen of X65 steel at the room temperature, 28 stainless steel at −20 to −250°C 31 and medium carbon steel at room temperature, 32 tensile testing of X70 steel under hydrogen at elevated temperatures (50 and 100°C) has not previously been reported. Since pipelines located in the desert environment are subject to deformation at low strain rates and can reach 50°C and over, the current work constitutes an attempt to simulate this service condition.…”
Section: Discussionsupporting
confidence: 86%
“…These observations indicate that the hydrogen-charged specimen tested at 100°C undergoes lower elongation before fracture than the argon-charged specimen at 25°C. These are consistent with results of Lee et al, 28 who conducted the same tensile test on X65 hollow cylindrical samples with hydrogen or nitrogen inside. They also found brittle fracture surface with almost no necking under hydrogen charging.…”
Section: Fractographysupporting
confidence: 92%
See 2 more Smart Citations
“…Perhaps the plastic deformation produced around these defects favored nucleation and propagation of internal and surface cracks, which contributed to the embrittlement of steel. This behavior is consistent with the literature, since many authors have reported the influence of hydrogen in the reduction in ductility and strength of steel [24][25][26][27] . Figure 9 shows the SEM micrographs of the fracture surfaces of the base metal (BM) test specimens, in asreceived (AR) condition.…”
Section: Effect Of Hydrogenation On Mechanical Propertiessupporting
confidence: 93%